2012
DOI: 10.1007/s10856-012-4644-0
|View full text |Cite
|
Sign up to set email alerts
|

Calcium alginate/dextran methacrylate IPN beads as protecting carriers for protein delivery

Abstract: In the present study, mechanical and protein delivery properties of a system based on the interpenetration of calcium-alginate (Ca-Alg) and dextran-methacrylate (Dex-MA) networks are shown. Interpenetrated hydrogels beads were prepared by means of the alginate chains crosslinking with calcium ions, followed by the exposure to UV light that allows the Dex-MA network formation. Optical microscope analysis showed an average diameter of the IPN beads (Ca-Alg/Dex-MA) of 2 mm. This dimension was smaller than that of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Expanded chondrocytes were entrapped in the IPN and it was demonstrated that the cells remained viable and were able to re-differentiate. In two follow-up studies, IPNs in the form of macroscopic gels and beads were obtained from partially oxidized Alg and methacrylated dextran and it was reported that these gels showed a faster degradation kinetics as compared to systems based on no oxidized Alg [42,97,98]. Very recently Fan and coworkers published a paper [99] on an IPN based on methacrylated Alg and collagen suitable for 3D pre-osteoblast spreading and osteogenic differentiation.…”
Section: Photopolymerized Alginate Ipnsmentioning
confidence: 99%
“…Expanded chondrocytes were entrapped in the IPN and it was demonstrated that the cells remained viable and were able to re-differentiate. In two follow-up studies, IPNs in the form of macroscopic gels and beads were obtained from partially oxidized Alg and methacrylated dextran and it was reported that these gels showed a faster degradation kinetics as compared to systems based on no oxidized Alg [42,97,98]. Very recently Fan and coworkers published a paper [99] on an IPN based on methacrylated Alg and collagen suitable for 3D pre-osteoblast spreading and osteogenic differentiation.…”
Section: Photopolymerized Alginate Ipnsmentioning
confidence: 99%
“…pH-responsive hydrogels have also attracted considerable interest given their capacity to reversibly respond to changes in environmental pH, which naturally undergoes substantial variations both as part of normal function (e.g., within the gastrointestinal tract or vagina) or as a response to a diseased state (e.g., in tumors or wounds). pH-responsive hydrogels have been applied to site-specific drug delivery in the stomach , or the colon, microenvironment-specific delivery responsive to disease, and to promote tissue regeneration through the controlled release of growth factors during cell maturation. , Most work on the use of such gels in biomedical applications has focused on cross-linking pH-sensitive natural (chitosan, , alginate) and/or synthetic (poly­(acrylic acid) (PAA), , polyethylenimine (PEI) and poly­(N,N′-dimethylaminoethyl methacrylate) (PDMAEMA)) , polymers, all of which have different p K a values, backbone hydrophobicities, and effective ionization ranges to enable tuning of the pH-driven response . Amphoteric gels that contain both cationic and anionic charges have attracted particular attention both due to their demonstrated capacity to suppress nonspecific protein adsorption (thought to be related to their protein-mimetic charge distributions) , as well as their ability to form ionic cross-links under near-neutral pH conditions in which both the cationic and anionic functional groups are charged, providing an additional cross-linking mechanism to enhance the mechanics of the resulting hydrogels.…”
Section: Introductionmentioning
confidence: 99%